-4(y-3)+2(3y-5)=11

Simple and best practice solution for -4(y-3)+2(3y-5)=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(y-3)+2(3y-5)=11 equation:


Simplifying
-4(y + -3) + 2(3y + -5) = 11

Reorder the terms:
-4(-3 + y) + 2(3y + -5) = 11
(-3 * -4 + y * -4) + 2(3y + -5) = 11
(12 + -4y) + 2(3y + -5) = 11

Reorder the terms:
12 + -4y + 2(-5 + 3y) = 11
12 + -4y + (-5 * 2 + 3y * 2) = 11
12 + -4y + (-10 + 6y) = 11

Reorder the terms:
12 + -10 + -4y + 6y = 11

Combine like terms: 12 + -10 = 2
2 + -4y + 6y = 11

Combine like terms: -4y + 6y = 2y
2 + 2y = 11

Solving
2 + 2y = 11

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 2y = 11 + -2

Combine like terms: 2 + -2 = 0
0 + 2y = 11 + -2
2y = 11 + -2

Combine like terms: 11 + -2 = 9
2y = 9

Divide each side by '2'.
y = 4.5

Simplifying
y = 4.5

See similar equations:

| m=1/4;(0,-2) | | 3=-7m | | -29.2=1.7+5.8+5.3n | | 7x+14=3x-12 | | 36Ln(36t+1)=19 | | A(5)+b=192 | | -.2=x-2.76/.64 | | 2x^2/10^3-2x^2 | | 14-12=x | | 3ln(1/x) | | 3(x+2)-4=x+2x+2 | | F(x)=3x^2+7x-6 | | x^3=578 | | 7x+y=-10x+6 | | 56/x-4 | | 4k-7k=(-20)-1 | | 7.5/50=c | | 7x-14=3x-4 | | 0.7x-1.4=0.3 | | x(3x+14)=-8 | | 1250+92*p=7000 | | 3(3)-2(1)= | | 5+14.50p=64 | | (w)(2w+8)2=26.25 | | (10-3)4+6= | | 4x+21y=229 | | 0.512*28=u | | 7.50+1.35t=12.90 | | u=p/n | | 68/x-4 | | y=3/4x-1/2 | | 2x+3y=6.50 |

Equations solver categories